Evaluasi dan Rekomendasi Usabilitas guna perbaikan E-Learning pada Perguruan Tinggi berdasarkan User Centered Design - Hulwah Zahidah; Amalia Rahmah (Jurnal Informatika Terpadu, 2020)
STT Terpadu Nurul Fikri is one of the institutions that utilize technology in developing teaching and learning activities using e-learning as the primary medium. However, the current condition of eLen still does not support student learning, as evidenced by the unavailability of several features needed by users. This support by the results of distributing questionnaires that refer to usability, that eLen has problems. With these problems, increasing the e-Len STT NF is necessary by designing a design solution based on user needs using User-Centered Design (UCD). User research will carry out; by making a prototype referring to user research results. The prototype that has been made will be tested using usability testing methods and a system usability scale. The results of usability testing state that the prototype of the eLen STT NF website that has been carried out based on UCD is quite good and is by user needs. Meanwhile, the System Usability Scale (SUS) results in a state that the SUS score from the UCD-based eLen STT NF website is 78.61. The next stage will be the implementation of Moodle, which will then be re-tested using the User Acceptance Test (UAT). Then the results from the UAT stated that the implementation of eLen STT NF was quite good; it obtains from the average test score based on 14 questions of 83.57%.